Escrow: International Experience and Perspectives of Application in Russia - MEDENTSEVA, Evgenia V.; TOKMAKOV, Maksim A. (Journal of Advanced Research in Law and Economics; Vol 8 No 3 (2017): JARLE Volume VIII Issue 3(25) Summer 2017, 2017)
Not long ago, the Russian legislation introduced the escrow institution, which has a long history in the foreign legal order and is actively used around the world for settlements and risk management. The escrow is quite a convenient and flexible legal instrument, the essence of which is that by the will of the parties between them there is one more entity – the so-called escrow-agent, who controls the fulfillment of the obligation by keeping the assets transferred under the condition. The popularity of such a design in the civil circulation of many foreign countries is conditioned by the analysis in the article of the prospects for the further development of the escrow institution in Russia. The paper presents foreign experience, in particular, the experience of the USA – the state in which the escrow has received the greatest development, and whose escrow model is traditionally taken as a model, suggests ways to improve the domestic legislation in order to bring to a certain unification with the world trends of development of law.